2011
DOI: 10.1097/eja.0b013e3283418fb0
|View full text |Cite
|
Sign up to set email alerts
|

Quality of pain management in the emergency department: results of a multicentre prospective study

Abstract: This multicentre study conducted on a nationwide scale shows that pain relief can be improved in the ED. Pain intensity is not sufficiently reassessed, analgesics are underutilised, morphine sulfate is rarely used and delay in treatment is common. Reasons for inadequate analgesia were identified in order to identify relevant corrective measures to improve quality of pain management in the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
0
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 31 publications
5
62
0
17
Order By: Relevance
“…En cuanto a los fármacos administrados, como sucede en los países de nuestro entorno, los AINE y paracetamol son los más utilizados, con bajo uso de opioides mayores, aunque superan a los reflejados en otros estudios (9). Actitudes como esperar a tener un diagnóstico y la opiofobia parecen seguir estando presentes.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…En cuanto a los fármacos administrados, como sucede en los países de nuestro entorno, los AINE y paracetamol son los más utilizados, con bajo uso de opioides mayores, aunque superan a los reflejados en otros estudios (9). Actitudes como esperar a tener un diagnóstico y la opiofobia parecen seguir estando presentes.…”
Section: Discussionunclassified
“…En cualquier caso, la presión asistencial se ha considerado que es un factor que puede influir negativamente en el adecuado control del dolor (9,12).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…3,6,7 However, two large multicenter studies have showed that pain scores are usually obtained only once in emergency department (ED) patients. 2,4 This suggests a lack of reassessment after initial treatment, which would presumably preclude implementation of analgesic titration. Such practice seems entirely plausible, given the difficulty of reassessment of patients' pain in an overcrowded ED.…”
mentioning
confidence: 99%
“…There is evidence that doses of analgesics given in practice are not large enough to achieve satisfactory analgesia for many patients. [1][2][3][4][5] Titration of analgesia appears to constitute the ideal strategy for management of acute pain. 3,6,7 However, two large multicenter studies have showed that pain scores are usually obtained only once in emergency department (ED) patients.…”
mentioning
confidence: 99%